SPACE LEXICALIZED: ITS LINGUISTIC IMPACTS IN ENGLISH AND ITS IMPLICATIONS FOR EFL LEARNING - A. Effendi Kadarisman (TEFLIN Journal: A publication on the teaching and learning of English, 2010)
Abstract: Our sense of space is part of our experiential universals.Â  However, the incorporation of space into words differs across languages.Â  This paper argues that âspaceâ is lexicalized in English but not in Indonesian.Â  English encodes the sense of location and direction into adverbial particles, producing language-specific expressions. Together with prepositions, adverbial particles also combine with simple verbs producing phrasal verbs and making a highly familiar verb expand itself into a huge range of meanings. Furthermore, the unique syntactic behavior of phrasal verbs is assumed to be the motivation for the phenomenon of âprepositional strandingâ in English. The enormous presence of adverbial particles in English and their absence in Indonesian could be problematic for Indonesian EFL learners. This problem can be viewed from two perspectives: inward & outward.